Assessment of serum prolactin level in hepatic encephalopathy patient - Giri, Richa; Pandey, Saksham; Kushwaha, J. S. (International Journal of Advances in Medicine, 2021)
Background: Hepatic encephalopathy (HE) is a complex neuropsychiatric disorder that arises in both acute and chronic liver disease. It is typified by the disturbance in consciousness and behavior, personality changes fluctuating neurological signs, asterisks or flapping tremors and distinctive EEG changes. This study was established to assess and evaluate the serum prolactin level in hepatic encephalopathy (HE) patient. Methods: The present cross-sectional study consisted a total 70 patients, out of those 35 were having HE and the rest 35 had no clinical evidence of HE. Those patients without clinical evidence of HE but having cirrhosis of liver, acute viral hepatitis and normal healthy controls. Results: Serum prolactin levels of patients of cirrhosis of liver with hepatic encephalopathy ranged from 37.6-210.7 ng/ml with a mean of 73.63±43.85 ng/ml. In patients, Prolactin levels were found significantly high in cirrhosis of liver patients with HE then cirrhosis of liver without HE patients (p<0.001). Level of serum prolactin in patients with hepatic encephalopathy with Fulminant hepatic failure (FHF) ranged from 30.6-119.7 ng/ml with a mean of 71.24±26.87 ng/ml. The values obtained from these are significantly higher as compared to those in normal healthy controls and those in acute viral hepatitis (p<0.001). Level of serum prolactin in patients of liver cirrhosis without hepatic encephalopathy ranged from 18.6-26.4 ng/ml with a mean of 21.48±2.43 ng/ml. These values are significantly higher than those found in normal healthy controls and those found in acute viral hepatitis (p<0.001). Mortality rate was 70% in patients of cirrhosis of liver with HE. Conclusions: Serum prolactin levels (SPL) are significantly higher in patients with complications such as hepatic encephalopathy and higher the levels, greater the severity. Hence, we conclude that level of serum prolactin can be used as a useful prognostic marker in patients with cirrhosis of the liver as well as an early indicator of its complications.